Effects of opioids administered via intravenous or epidural patient-controlled analgesia after caesarean section: a network meta-analysis of randomised controlled trials. (February 2023) - Chang, Chun-Yu; Tu, Yu-Kang; Kao, Ming-Chang; Shih, Ping-Cheng; Su, I-Min; Lin, Han-Yu; Chien, Yung-Jiun; Wu, Meng-Yu; Chen, Chih-Hao; Chen, Chu-Ting
Summary: Background: Post-caesarean section analgesia is important physiologically and psychologically for both mothers and infants. Patient-controlled analgesia is a well-established method of administering opioids for postoperative pain. However, to date, no study has systematically investigated the effects of opioids administered through intravenous patient-controlled analgesia (IVPCA) or patient-controlled epidural analgesia (PCEA) in parturients who have undergone caesarean section. Methods: This systematic review and network meta-analysis aimed to evaluate the analgesic and adverse effects of opioids administered via IVPCA or PCEA in parturients who have undergone a caesarean section. PubMed, Embase, Scopus, Web of Science, and Cochrane Library were searched from inception through 02 10, 2022 for relevant records. Randomised controlled trials (RCTs) that compared opioids administered via IVPCA or PCEA and reported outcomes of interest were included. Studies were excluded if the solution for patient-controlled analgesia contained antiemetics and/or other analgesics in addition to opioids. The methodological quality of RCTs was assessed using the revised Cochrane Risk of Bias Tool. Summary data were extracted from each eligible study. The primary outcome was pain intensity, and the secondary outcomes were opioid-related adverse effects. Frequentist network meta-analyses were performed using a contrast-based random-effects model. This study is registered with PROSPERO, CRD42021254040. Findings: Twenty-three studies with 2589 parturients were included. Compared with IVPCA morphine as a reference treatment, PCEA fentanyl had better analgesic effects at 4 h (mean difference [MD] in the visual analogue scale score, −0.75; 95% confidence interval [CI] [-1.16, −0.34]) and 8 h (MD, −0.93; 95% CI [-1.57, −0.28]) and yielded lower odds of developing nausea/vomiting (odds ratio [OR], 0.27; 95% CI [0.09, 0.80]) and sedation/drowsiness (OR, 0.22; 95% CI [0.11, 0.45]). However, PCEA fentanyl may be more likely to cause pruritus than IVPCA treatments. Interpretation: Considering the analgesic efficacy; opioid-induced nausea, vomiting, and sedation; and the well-being of breastfed infants, PCEA fentanyl may be the treatment of choice for post-caesarean section analgesia. Funding: The Taipei Tzu Chi Hospital, Buddhist Tzu Chi Medical Foundation (TCRD-TPE-111-27)